Integration of human factors in design of high performance sports products - Kaneko, Y. (5. Asia-Pacific Congress on Sport Technology 2011 Melbourne, 2011)
Sports products desiign Integration of mechanical factor Integration of biomechanical factor Integration of psychological factor Integration of human factor with variability Integration of brain processing factor